Применение резонаторного микрозонда для определения влагосодержания в биообъектах - Гордиенко, Ю. Е.; Старостенко, В. В.; Полетаев, Д. А. (ХНУРЭ, 2009)
The basic directions of optimization resonator microprobe for bioobject's microwave scanning microscopy are analysed by means of methods of direct numerical modelling. In work the obvious kind of function, invariant concerning size of a backlash between an end face of the aperture and the sample is found. Introduction of the given function will allow to minimize the error of measurement.
Keywords: резонаторный микрозонд; влагосодержание в биообъектах